ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus pada Rumah Makan "Rata-Rata" Yogyakarta) - Suseno Hendratmoko (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This research aims to determined customer satisfaction with the quality product, service quality and price at restaurant Rata - rata Yogyakarta. This research is a type of quantitative descriptive used primary and secondary data. The technic use accidental sampling with sampling. Research gives shows better quality, gives more satisfaction to customers. Even in service quality. Better service quality gives more customer satisfaction. So that with the variable of price. With the competitive price, gives more customers satisfaction. It shows that even both partially nor simultaneusly, product quality, service quality and price give effects to the customers satisfaction. Especially for product quality has highest validity. It's about 0,413 or 41,3 % effect to custome satisfaction. As it has the tagline of the restaurant; serv all indonesian taste vegetable soup with 25varians, 45 dining fish.